Pest risk assessment of Dracaena reflexa for market access of its cut foliage to European Union and Japan - Susheela, K; Sathyanarayana, N (Indian Journal of Plant Protection, 2020)
Kadiyam Mandal located in East Godavari district of Andhra Pradesh, is a hub for production of wide variety of ornamental plants. Most of the production is for domestic market. Assessment is initiated to explore the potential of Kadiyam nurseries to export cut foliage to European Union and Japan as they are the leading importers. Hot and humid weather at Kadiyam is congenial for production of cut foliage throughout the year. Among the cut foliage species, Dracaenas occupy prime place in international trade. Dracaena (Song of India), which is the most commonly grown species at Kadiyam nurseries is chosen for further evaluation. Sanitary and Phytosanitary (SPS) requirements of the importing countries need to be met for market access. Present study evaluates the risk assessment w.r.t production practices, prevalence of pests and risk mitigation options for safe export of cut foliage. Assessment for the weedy potential of D. reflexa, indicated that the weedy potential of this species is not recorded anywhere. Among the pests and diseases recorded on D. reflexa in India, Pantoea stewartii for European Union (EU) and Japan; Chaetanaphothrips signipennis (Banana thrips), Nipaecoccus nipae (Spiked mealy bug) and Pseudococcus jackbeardsleyi for Japan are found to have actionable regulatory status. Evaluation of these pests weighing against existing production methods at production site, Kadiyam, indicated that the risk potential associated with the export of D. reflexa cut foliage is low and warrants no specific phytosanitary measures beyond inspection at port-of-entry. However, the existing production methods warrant implementation of good production, s to ensure quality, hygiene, health and to meet phytosanitary requirements. Several events in the export chain from production, post-harvest and until shipping are discussed, and appropriate technical and policy interventions are suggested to gain market access.